Adipose-Derived Stem Cell Modulation of T-Cell Regulation Correlates with Heme Oxgenase-1 Pathway Changes. Issue 5 (November 2016) - Chien, Ching-Ming; Chen, Yung-Wei; Chen, Chien-Chang; Wu, Yi-Chia; Huang, Shu-Hung; Lee, Su-Shin; Lai, Cheng-Sheng; Lin, Sin-Daw; Wang, Ching-Jen; Kuo, Yur-Ren
Abstract : Background: The authors' previous proteome study revealed that haptoglobin was involved in adipose-derived stem cell modulation of allotransplant survival and T-cell regulation to induce immune tolerance. This study investigated whether adipose-derived stem cells could modulate T-cell regulation through haptoglobin and the downstream heme oxgenase-1 pathway in vitro. Methods: Splenocytes were isolated from Lewis rat spleens and then CD3 + T cells were purified using anti-CD3 + beads. Adipose-derived stem cells were harvested from Lewis rats and co-cultured with the T cells. After Transwell co-culture at different periods, the authors analyzed cell proliferation with a bromodeoxyuridine assay. Cell extractions and culture supernatants were collected for further analysis. Heme oxgenase-1 and related protein expression levels from the adipose-derived stem cells and T cells were detected using Western blotting. The related cytokine expression levels were analyzed with enzyme-linked immunosorbent assay kits. Flow cytometry was used to detect the regulatory T-cell proportion. Results: The adipose-derived stem cells significantly suppressed T-cell proliferation. The regulatory T-cell percentages were significantly increased in the adipose-derived stem cells that were co-cultured with T cells compared with T cells alone without adipose-derived stem cell co-culture. Heme oxgenase-1 expression in concanavalin A–stimulated T cells that were co-cultured with adipose-derived stem cells revealed a significant increase compared with concanavalin A–stimulated T cells alone. Cytokine assays of the culture supernatants revealed that transforming growth factor-β and interleukin-10 were significantly increased and interferon-γ was statistically decreased in the adipose-derived stem cell–co-cultured T-cell group compared with other groups; however, blockade with a heme oxgenase-1 inhibitor (zinc protoporphyrin IX) protected against these changes. Conclusion: Adipose-derived stem cells modulate T-cell proliferation and enhance regulatory T-cell expression, and this correlated with heme oxgenase-1 expression and related cytokine pathway changes.